Resilience of German regions to climate change - Britta Stöver; Florian Bernardt (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2023)
There is broad agreement in the scientific community that climate change has already advanced significantly compared to pre-industrial times and will continue to increase due to past emissions of greenhouse gases (GHGs). As a consequence, extreme weather events will become more probable, more frequent and more severe affecting all areas of life, the environment and the economy. Additionally, extreme weather events occur on a local level forcing regions and cities to advance the impacts of climate change. One important concept to measure the robustness of a city or smaller geographic area towards climate change is resilience. Though the term and concept of resilience is not uniquely defined it is often used in this context to express the ability of the local identity to cope, withstand and adapt to the challenges posed by an extreme event. The objective of this paper is to assess the resilience of German regions to extreme weather events caused by climate change. Scenario results depicting the impact of climate change from the national macro-econometric model INFORGE were linked to the regional model QMORE. The model results were used to derive indicators that assess the resistance of German regions against climate change. The regions were divided into groups using cluster analysis to detect determinants that explain higher or lower sensitivity towards climate change. Finally, the implementation of climate change adaptation measures were assessed with regard to resistance as an indirect measure for recovery. It shows that there was a clear division with regard to sensitivity to climate change: Regions in the north-west and south-east were considerably less resistant to climate change impacts. However the determinants for high resistance were not that clear cut. Regions seem to be more resistant if they were only confronted with one challenge, i.e. if labour market shortages does not add to the impact of climate change and if the agricultural sector is of lower importance. Climate change adaptation helps in strengthening resistance against climate change. However, the measures should be tailored to the specific local situation to be more effective. Otherwise, with an unspecific distribution, the regions that need adaptation and an increase in resilience most were not necessarily addressed.
Keywords: R11; R15; Q51; C67; 330; resilience; regions; climate change; climate change adaptation